DGCR8/miR-106 Axis Enhances Radiosensitivity of Head and Neck Squamous Cell Carcinomas by Downregulating RUNX3 - Zhang, Chunlin; Chen, Hangqi; Deng, Zeyi; Long, Dan; Xu, Li; Liu, Zhaohui (Frontiers in Medicine, 2020)
Purpose: Head and neck squamous cell carcinoma (HNSCC) is the 6th malignant tumors worldwide and the radiotherapy effect is strongly associated with HPV infection. Therefore, the aim of our study was to analyze the mechanism of HPV E7 and its effects of the radiosensitivity in HNSCC cells. Methods: The mRNA expression of DGCR8, has-miR-106a and RUNX3 was examined by quantitative real-time PCR (RT-qPCR). The protein expression of DGCR8, E7, RUNX3, Caspase3/cleaved Caspase3, PARP/cleaved PARP, γH2AX was measured by western blot. The expression level of DGCR8 was measured by immunofluorescence assay. Starbase database (http://starbase.sysu.edu.cn/) was used to analyze the correlation between has-miR-106a-5p and DGCR8. TargetScan database (http://www.targetscan.org/vert_72/) database was adopted to calculate the prediction of binding sites. Radiosensitivity was evaluated through clone formation assays and CCK-8 assays. Results: In our study, we found that the mRNA and protein expression levels of HPV E7 and DGCR8 in HPV-positive HNSCC cells were higher than that in HPV-negative cells. The expression of DGCR8 was increased in FaDu and UM-SCC-4 with E7 overexpression while the expression of DGCR8 was decreased in UM-SCC-47 and UPCI-SCC-090 with E7 silence. The miR-106a expression was increased after DGCR8 overexpression in FaDu and UM-SCC-4. However, the miR-106a expression was decreased in UM-SCC-47 and UPCI-SCC-090 with E7 silence. In radiation conditions, clone formation assays found that less clones formed in FaDu and UM-SCC-4 cells subsequent to silencing DGCR8 or miR-106a than that in the control group, and more clones were formed in UM-SCC-47 and UPCI-SCC-090 cells overexpressing DGCR8 or miR-106a than that in the control group. Luciferase reporter gene assays verified that miR-106a targeted the 3’UTR of RUNX3 mRNA. MiR-106a overexpression resulted in a decrease in RUNX3 expression and miR-106a silence increased RUNX3 expression. Rescue experiments conducted with miR-106a inhibitor restored radiation resistance and reduced DNA damage in radiation condition. Conclusions: Our study indicated that HPV E7 activated DGCR8/miR-106a/RUNX3 axis to enhance radiation sensitivity and provided directions for targeted therapeutic interventions.